ANALYSIS TO DECREASE DEATH ON ARRIVAL OF ORNAMENTAL FISH USING HR SCORECARD - Tje Fie, Tjhie
PT X is a large ornamental fish exporting company in Indonesia, with a large market growth and one of the challenges that must be faced is the death of fish upon arrival in the consumer country. Fish mortality rates that exceed the target (3.5%) and tend to rise will be a burden on the company. Fish mortality rates called Death on Arrival (DOA) have many complexity factor because align with many departments, system performance management, and human skill so that requires a strategic management approach. Thus, this study aims to see whether PT X has applied strategic management in reducing fish mortality, and whether the application of the HR Scorecard system is the right system and how are the steps to implement it. This study start with exploring HR Scorecard and find there is 7 steps of HR Scorecard implementation, based on that’s step this research make a design of questioner and survey to PT X. Also Exploring HR Scorecard with some literature review to make a Design of HR Scorecard Implementation. Using Gap Analysis to find what is the gap between Current HR Scorecard Implementation and Design HR Scorecard Implementation From the results of this study using gap analysis, it is known that the application of the 7 steps of the HR Scorecard found 5 gaps to be improve. The 7 steps of the HR Scorecard Implementation can be seen as more strategic choice to reducing fish mortality; this is because the 7 steps of the HR Scorecard have been able to regulate many factors needed to reduce the number of DOA